Desalination: conversion of seawater to freshwater - Bahar, Rubina; Hawlader, Mohammad Nurul Alam (2013)
Desalination methods are used to convert saline/brackish water to drinkable freshwater. Major processes use either thermal energy (conventional distillation) or pressure energy (Reverse osmosis). Different methods of desalination are discussed and their influence on overall water production has been highlighted. With the increase in appreciation for a green technology, desalination methods using renewable/waste energy are drawing significant attention in recent years. Applying different methods of desalination for coastal areas in Peninsular Malaysia can be very promising in terms of overall public health and economy.